PENGARUH MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS CERITA FANTASI SISWA KELAS VII SMP NEGERI 10 PADANG - Silvana, Nola; Basri, Irfani; Emidar, Emidar (Universitas Negeri Padang, 2018)
ABSTRACTThis research aims to describe the influence model of discovery learning the skills of writing text exposition class VII SMP Negeri 10 Padang. The type of this research is quantitative research done using experimental design. The results of this research are three: (1) writing text skills exposition before using discovery learning model of class VII SMP Negeri 10 Padang are in qualifying Nearly Enough (HC) with an average value of 61,49, (2) writing text skills exposition after using discovery learning model of class VII SMP Negeri 10 Padang are in qualification More than Enough (HC) with an average value of 72,41, and (3) exposition writing text skills class VII SMP Negeri 10 Padang after using the model of discovery learning better than before using the model of discovery learning.Â Kata Kunci: pengaruh, model discovery, teks cerita fantasi